Conjugated linoleic acid (CLA) and polyunsaturated fatty acids in muscle lipids of lambs from the Patagonian area of Argentina - Garcia, Pilar Teresa (2007)
The concentrations of fatty acids were measured in total lipids, triacyglycerol and phospholipid fractions of intramuscular fat (IMF) from the Longissimus dorsi (LD) muscle of 10 lambs reared to approximately 30 kg live weight on natural pasture with their dams. Fatty acid composition was also measured in 25 (five of each) Semitendinosus (ST), Semimembranosus (SM), Rectus femoris (RF), Gluteus (GLU) and Tensor fascia latea (TFL) muscles. Intramuscular fat percentages were similar for all muscles. Aspects of the fatty-acid patterns of relevance to human nutrition tended to favor the leg muscles with lower saturated fatty acids (SFA %), n−6/n−3 fatty acid ratios (p < 0.01) and higher concentrations of the conjugated linoleic acid (CLA) (p < 0.05). The estimated fatty acid concentrations (mg/100 g of meat) showed higher contribution of arachidonic (C20:4 n−6), eicosapentanoic (C20:5 n−3), docosapentanoic (C22:5 n−3) and docosahexanoic (C22:6 n−3) acids in leg compared to LD lipids.